A Great Masquerader: Nasal Type, Extranodal Natural Killer/T-cell Lymphoma Presenting as Recalcitrant Bacterial Sinusitis and Periorbital Cellulitis - Zaw Min; Nitin Bhanot (Case Reports in Medicine)
Nasal extranodal natural killer/T-cell lymphoma (ENKL) is a rare clinical entity. It may, however, masquerade as a commonly encountered disease, such as sinusitis. A high index of clinical suspicion of nasal ENKL should be raised when there is inadequate clinical response despite appropriate therapeutic intervention of sinusitis. Biopsy would be warranted and crucial in those instances to make an accurate and timely diagnosis.